Bloodstream infections in Injecting drug users: A 15 year prospective single-centre study. (November 2022) - Allen, Victoria B.; Bechman, Katie; Klein, John L.
Highlights: IDUs accounted for nearly 8% of all community acquired bloodstream infections. S . aureus and S. pyogenes were the most common pathogens. The commonest foci of infection were skin/soft tissue and septic thrombophlebitis. Infective endocarditis was relatively uncommon but was associated with mortality. Septic thrombophlebitis caused more septic pulmonary emboli than endocarditis. Abstract: Objectives: To describe the microbiological and clinical characteristics of bloodstream infections (BSIs) in Injecting Drug Users (IDUs). Methods: All episodes of community-acquired BSI in IDUs were reviewed. Demographic, clinical and microbiological data were analysed. Detailed analyses were performed for septic thrombophlebitis and infective endocarditis (IE). Historical analysis of microbiological characteristics of BSIs from 1970 to 2018 was performed. Results: There were 406 episodes of BSI in IDUs accounting for 7.8 % of community-acquired BSIs from 2004 to 2018. Patients were male in 77.3 % of episodes. Median age was 38.1 years. Positive HIV status was confirmed in 14 % of episodes. The commonest infecting species were Staphylococcus aureus (45.8 %) and Streptococcus pyogenes (11.8 %). Polymicrobial BSIs accounted for 20.2 % of infections; other streptococci (12.8 %), gram-negative bacilli (4.9 %) and anaerobes (2.7 %) accounted for most of the remainder. The commonest foci of infection were skin and soft tissue (26.4 %), septic thrombophlebitis (20.4 %), bone and joint (17.5 %) and IE (11.8 %). Overall inpatient mortality was 5.9 %. IE and necrotizing fasciitis were associated with increased risk of death. Conclusions: IDUs accounted for a significant proportion of community-acquired BSIs. Skin and soft tissue infection and septic thrombophlebitis were the commonest foci of infection. IE is rare, but mortality is high.